Enterprenuerial Motivation Amongst University Students in Pakistan: Proposing and Testing a Mediation Model - Muhammad Ali Ahmad; Syed Alamdar Ali Shah; Waqar Ahmed Mallah; Muhammad Saud (Program Studi S3 Ilmu Manajemen, 2019)
Objective of this research is to explore factors that contribute towards entrepreneurial motivation amongst university students in Pakistan. Data of 500 respondents from HEC recognized universities in Pakistan has been collected and analyzed for the purpose of our research. Data has been gathered from students of different degree programs commerce, business administration, banking and finance, and marketing department of public and private universities of Pakistan. A mediation model has been proposed and tested in order to achieve our objectives. Data has been analyzed using different econometric and statistical techniques. The results suggest that there exists some Ã¢â‚¬Å“psychologicalÃ¢â‚¬Â and Ã¢â‚¬Å“economicÃ¢â‚¬Â factors that influence the entrepreneurial motivation of university students in Pakistan. Over and above, there also that exits a group of psychological factors that partially mediate in our model.